Architecture as a response to the challenges of modernity - Volichenko, Olga (project baikal, 2023)
Consideration of the evolution of architecture of the 20-21st centuries through the prism of the world global crises allows us to feel the influence of economic and political cataclysms on the formation of modern architectural theory and practice. Being a kind of mirror, architecture reflects all the current problems that worry and excite the society, so architects have always been deeply involved in crisis problems and have sought to find ways out of them by means of the architectural profession. Each global crisis of the past and present centuries became a turning point in the development of architecture and urban planning, forming new stylistic, conceptual and theoretical trends of modernism, postmodernism and panmodernism. The concept of “panmodernism” indicates the universal nature of modernism, covering all the diversity of architectural mainstreams that arise as a response of architects to the crisis problems of modernity.
Keywords: modernism; constructivism and functionalism; Athens Charter; brutalism; postmodernism; architectural mainstream; panmodernism